Development of a novel control strategy for a multiple-circuit roof-top bus air-conditioning system in hot humid countries - Khamis Mansour, M.; Musa, Md. N.; Hassan, M. N. W.; Abdullah, H.; Saqr, K. M. (University of Malaya, 2007)
A novel control strategy to improve energy efficiency and to enhance passengers' thermal comfort of a new roof-top bus multiple-circuit air-conditioning (AC) system operating on partial load conditions is presented. The new multiple-circuit AC system consists of two evaporators, two condensers, two expansion valves, and two equal capacity compressors. Each one of the evaporators is split up into two halves, one-half of the evaporator coil of one circuit pairing with one-half of the other circuit. A novel strategy for an automatic control of the AC system was developed based on numerous experimental test runs at various operating conditions, taking into account energy saving and thermal comfort without sacrificing the proper cycling rate of the system compressor. For this task, more than 50 test runs were conducted at different set-point temperatures of 21, 22, and 23Â°C. Fanger's method was used to evaluate the passenger thermal comfort and the system energy consumption was also calculated. A performance comparison between that of the conventional AC system and the newly developed one has been conducted. The comparison revealed that the adopted control strategy introduces significant improvements in terms of thermal comfort and energy saving on various partial load conditions, with potential energy saving of up to 30.8% could be achieved. This results in a short payback period of 19 months. It was found from the economic analysis that the new system is able to save approximately 19.7% of the life cycle cost.